Analysis of buffeting response of hinged overhead transmission conductor to nonstationary winds. (15th September 2017) - Wang, Dahai; Chen, Xinzhong; Xu, Kang
Highlights: Buffeting response analysis of a hinged conductor under non-synoptic wind excitations was presented. The time-varying mean response is determined by nonlinear static analysis with an analytical solution. Formulations are presented for calculating time-varying standard derivation of response and extreme response distribution. The effectiveness and accuracy of the proposed framework are verified through response time history analysis using a finite element model. The response characteristics of conductor under various nonstationary winds are examined through a parametric study. Abstract: This paper addresses analysis of dynamic buffeting response of a hinged transmission line (conductor) under nonstationary wind excitations. The nonstationary wind speed is characterized by deterministic time-varying mean and stochastic fluctuating components. The wind load on the conductor is quantified using quasi-steady theory. The wind-induced response of the conductor is decomposed into deterministic time-varying mean and stochastic dynamic components. The time-varying mean response is determined by nonlinear static analysis with an analytical solution. The stochastic dynamic response is determined through quasi-static analysis in terms of influence function around the time-varying mean equilibrium. A closed-form formulation is presented for calculating time-varying standard derivation of response. The cumulative distribution function of the extreme response over a given time duration is then calculate using mean upcrossing rate theory of nonstationary random process. The effectiveness and accuracy of the proposed analytical framework are verified through response time history analysis using a nonlinear finite element model. The response characteristics of conductor under various nonstationary winds are examined through a parametric study.